Amplified Detection of Iron Ion Based on Plasmon Enhanced Fluorescence and Subsequently Fluorescence Quenching - Zhou, Lin; Zhang, Han; Luan, Yanping; Cheng, Si; Fan, Li-Juan (Nano-Micro Letters, 2014)
A facile and rapid approach for detecting low concentration of iron ion (Fe3+) with improved sensitivity was developed on the basis of plasmon enhanced fluorescence and subsequently amplified fluorescence quenching. Au1Ag4@SiO2 nanoparticles were synthesized and dispersed into fluorescein isothiocyanate (FITC) solution. The fluorescence of the FITC solution was improved due to plasmon enhanced fluorescence. However, efficient fluorescence quenching of the FITC/Au1Ag4@SiO2 solution was subsequently achieved when Fe3+, with a concentration ranging from 17 nM to 3.4 μM, was added into the FITC/Au1Ag4@SiO2 solution, whereas almost no fluorescence quenching was observed for pure FITC solution under the same condition. FITC/Au1Ag4@SiO2 solution shows a better sensitivity for detecting low concentration of Fe3+ compared to pure FITC solution. The quantized limit of detection toward Fe3+ was improved from 4.6 μM for pure FITC solution to 20 nM for FITC/Au1Ag4@SiO2 solution.